(untitled) (Vietnam Journal of Community Medicine, 2026)
Introduction: Human fascioliasis is one of the neglected infectious diseases that is now emerging and re-emerging with increasing infection rates in several regions worldwide, and Vietnam is one of the countries with the highest infection rate. B-mode ultrasound helps diagnose and monitor the recovery phase after specific treatment, but it cannot assess the degree of liver parenchyma fibrosis (stiffness) and damage to the hepatobiliary system during Fasciola spp. infection. Fibroscan is a modern tool used to assess the degree of liver fibrosis (stiffness) of parenchyma lesions, helping to monitor the recovery of liver parenchyma in the hepatobiliary system. The objective of this study was to evaluate changes in hepatobiliary system damage caused by Fasciola spp. on B-mode ultrasound and fibroscan, and to monitor the liver fibrosis stage of liver lesions before and after treatment through liver parenchymal stiffness. Methods: A cross-sectional descriptive design with case series was used to characterize hepatobiliary lesions caused by Fasciola spp. on ultrasound and to assess changes in hepatobiliary lesions before and after treatment with triclabendazole 20 mg/kg. The study recorded 40 cases of fascioliasis with liver lesions on ultrasound and characterized the hepatobiliary lesions, including the stage of liver fibrosis, before and after treatment at 1 and 3 months. Results: The most common location of Fasciola spp. lesions were the right lobe (62.5%), less common in the left lobe (27.5%), and in both lobes (10%). The number of lesions was mainly 1 lesion (50%) and 2 lesions (40%). The largest diameter of the lesion was usually 30-70 mm (65%). The most common echogenicity of fascioliasis lesions was typical mixed echogenicity consisting of predominantly hypoechoic, with added hyperechoic and anechoic (70%), followed by atypical mixed echoic lesions (hypoechoic with added hyperechoic) at 30%, and the least common was purely hypoechoic lesions (10%). Fibroscan assessing the stiffness (fibrosis) of fascioliasis-like lesions according to Metavir score showed that F2 accounted for a high percentage (82.5%), followed by F1 (17.5%), while the stiffness of the unaffected liver area was mostly at F0 (92.68%), with F1 accounting for a low percentage (7.32%). After 1 and 3 months of treatment, the number and diameter of fascioliasis lesions mostly decreased. The echogenicity of the lesions changed from mixed echogenicity with predominantly hypoechoic to hyperechoic after 3 months of treatment. The stiffness of the lesion changed during treatment: after 1 month, the stiffness of the liver lesion area changed from F2 (82.5%), F1 (17.5%) to F3 (85%) and F4 (7.5%), F2 (7.5%); after 3 months, the stiffness increased to F4 (30%), while F3 remained high (70%). This demonstrates the presence of liver fibrosis in the lesions caused by Fasciola spp. during the recovery phase. Conclusion: Liver fibroscan combined with B-mode ultrasound supports the diagnosis and differentiation of atypical liver lesions caused by Fasciola spp. from other liver lesions more accurately. During the recovery phase, liver fibrosis should be monitored.